O único luxo de um santo laico: fotografias em biografias de Clóvis Beviláqua - Silva, Wilton Carlos Lima da [UNESP] (My University, 2013)
The jurist Clovis Bevilaqua (1859-1944) was a privileged member of a political and intellectual elite in the context of the transition from the nineteenth to the early decades of the twentieth century in this country, having been a professor at the Faculdade de Direito de Recife, author of the Civil Code of 1917, consultant for the Ministério das Relações Exteriores and jurist of international prestige, and literary critic and author of law, philosophy and history.Their biographies emphasize the breadth of his legal knowledge, the merits of civil codification which was author and lifestyle humble and generous earning him the nickname "secular saint". However, the lawyer had the habit of collecting photos of himself and of his family and this behavior is characterized as a single vanity for his biographers. From four biographies of Clovis Bevilaqua, written by Lauro Romero (1956), Raimundo de Menezes and Ubaldino de Azevedo (1959), Noemia Paes Barreto Brandão (1989) and Silvio Meira (1990), we intend to discuss how these images are used to illustrate the trajectory of the jurist and corroborate the distinct narratives models.

O jurista Clóvis Beviláqua (1859-1944) ocupou posição privilegiada entre os “brasileiros notáveis” do contexto de transição do século XIX para as primeiras décadas do século XX no Brasil, como membro destacado de uma elite política e intelectual, tendo sido professor na Faculdade de Direito de Recife, autor do Código Civil de 1917, consultor do Ministério das Relações Exteriores e jurista de prestígio internacional, além de crítico literário e autor de livros de direito, filosofia e história. Suas biografias enfatizam a amplitude de seus conhecimentos jurídicos, os méritos da codificação civil da qual foi autor e o modo de vida humilde e generoso que lhe valeu a alcunha de “santo laico”. No entanto, o jurista cultivava o hábito de colecionar fotos de si e de sua família, comportamento que um de seus biógrafos caracterizou como sua única vaidade. A partir de quatro biografias de Clóvis Beviláqua, escritas por Lauro Romero (1956), Raimundo Menezes e Ubaldino de Azevedo (1959), Noemia Paes Barreto Brandão (1989) e Silvio Meira (1990), pretendemos discutir como essas imagens são utilizadas para ilustrar a trajetória do jurista e corroborar as distintas matrizes narrativas.
The one luxury of a secular saint: personal photographies in biographies of Clovis Bevilaqua
Keywords: Clovis Bevilaqua; Biography; Photography; Clóvis Beviláqua; Biografia; Fotografia